Design and Fabrication of Segmented GeTe/(Bi,Sb)2Te3 Thermoelectric Module with Enhanced Conversion Efficiency - Pei, Jun; Shi, Jian‐Lei; Li, Hezhang; Jiang, Yilin; Dong, Jinfeng; Zhuang, Hua‐Lu; Cai, Bowen; Su, Bin; Yu, Jincheng; Zhou, Wei; Zhang, Bo‐Ping; Li, Jing‐Feng (Advanced functional materials, 2023)
GeTe and (Bi,Sb)2Te3 are two representative thermoelectric (TE) materials showing maximum performance at middle and low temperature, respectively. In order to achieve higher performance over the whole temperature range, their segmented one‐leg TE modules are designed and fabricated by one‐step spark plasma sintering (SPS). To search for contact and connect layers, the diffusion behavior of Fe, Ni, Cu, and Ti metal layers in GeTe is studied systematically. The results show that Ti with a similar linear expansivity (10.80 × 10−6 K−1) to GeTe, has low contact resistance (3 µΩ cm2) and thin diffusion layer (0.4 µm), and thus is an effective metallization layer for GeTe. The geometric structure of the GeTe/(Bi,Sb)2Te3 segmented one‐leg TE module and the ratio of GeTe to (Bi,Sb)2Te3 are determined by finite element simulation method. When the GeTe height ratio is 0.66, its theoretical maximum conversion efficiency (ηmax) can reach 15.9% without considering the thermal radiation and thermal/electrical contact resistance. The fabricated GeTe/(Bi,Sb)2Te3 segmented one‐leg TE module showed a ηmax up to 9.5% with a power density ≈ 7.45 mW mm−2, which are relatively high but lower than theoretical predictions, indicating that developing segmented TE modules is an effective approach to enhance TE conversion efficiency. GeTe/(Bi,Sb)2Te3 segmented one‐leg thermoelectric modules are successfully designed and fabricated. Its maximum efficiency reaches 9.5 % under the adiabatic boundary condition of cold side heat flow via Mini‐PEM, indicating a good application prospect.